LEVEL OF KNOWLEDGE OF ELEMENTARY SCHOOL CHILDREN ABOUT THE DANGERS OF SMOKING AT SD NEGERI 9 RAPE RAPE - Jasmine, Audry Azila; Mokhtar, Shulhana; Darma, Sidrah; Anggita, Dwi; Hadi, Santriani (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2026)
Smoking is a habit that has a negative impact on health, but now many children are starting to smoke from an early age. Elementary school children aged 6–12 years are in the process of forming basic knowledge, including an understanding of the dangers of smoking. This study aims to assess the level of knowledge of students at SD NEGERI 9 RAPE-RAPE about the dangers of smoking. This descriptive study with a cross-sectional design involved 83 respondents selected using total sampling and a questionnaire that had been tested for validity and reliability. Data analysis was performed descriptively using frequency distribution and ANOVA tests. The results showed low knowledge about smoking (84.3%) and the dangers of smoking (57.8%), with significant differences between classes (p<0.05). These findings indicate the need to improve health education and integrate material on the dangers of smoking into elementary school learning.